Parents' Habits in Instilling Empathy Behaviors in Children Aged 4-6 Years - Nova Christina Christina; Krisna Ivarianti; Khairunnisa Nazwa Kamilla; Nayla Aura Alifia; Mayang Rezha Yolandha; Febry Maghfirah (Universitas Al-Hikmah Indonesia, 2025)
This research discusses the importance of the role of parents in instilling values of empathy and helping behavior in children from an early age through habits formed in the family environment. The aim of this research is to understand how parental involvement affects the development of children's empathy in daily life. The research was conducted using a qualitative approach with a case study method, employing data collection techniques such as observation, interviews, and documentation. The results show that the research subjects, Ananda M and X, have a high level of empathy, especially in helping behavior. This is influenced by the habits and role models consistently provided by parents at home. The discussion of the results indicates that a warm, emotionally supportive family environment that provides real examples of empathetic behavior plays a crucial role in shaping a child's caring and loving character.